Umbilical cord blood interleukin-6 level as a predictor of early-onset neonatal sepsis - Arya Adnan Fadilah; Ekawaty Lutfia Haksari; Setya Wandita (Indonesian Pediatric Society, 2022)
Background Neonatal sepsis is a global health problem contributing significantly to neonatal morbidity and mortality. It is difficult to clinically distinguish neonates with and without sepsis. Interleukin-6 (IL-6) concentration in neonates has high sensitivity and specificity to predict neonatal sepsis in infants at risk. Objective To determine the utility of umbilical cord blood IL-6 as a predictor of early-onset neonatal sepsis. Methods This prospective cohort study was conducted in neonates born to mothers with sepsis risk factors from December 2020 to January 2021. We measured IL-6 from umbilical cord blood taken after placental expulsion. IL-6 ³16.4 pg/ml was considered to be elevated. Subjects were monitored for signs of clinical sepsis until 72 hours after birth. We also recorded the presence of other maternal and infant risk factors of sepsis and assessed association between IL-6 and other risk factors with the occurrence of sepsis, expressed as relative risk (RR) with 95% confidence interval (95%CI). Results During the study period, 40 neonates were born to mothers with sepsis risk factors; 13 (32.5%) developed clinical sepsis. Significantly more infants with elevated IL-6 developed neonatal sepsis (55.5%) than those with normal IL-6 (13.6%). After multivariate analysis incorporating other significant variables, the risk factors predictive of clinical early-onset neonatal sepsis were IL-6 [RR 5.54 (95%CI 1.68-18.25); P=0.016], prematurity [RR 4.92 (95%CI 1.66-14.59); P=0.014], and initial Apgar score [RR 3.38 (95%CI 1.34-3.38); P=0.046]. Conclusion In neonates with maternal risk factors, an IL-6 level of ³16.4 pg/ml is associated with an increased risk of early-onset neonatal sepsis.